Exploring the Bioactive Potential and Chemical Profile of Schinus molle Essential Oil: An Integrated In Silico and In Vitro Evaluation - Rómulo Oses; Matías Ferrando; Flavia Bruna; Patricio Retamales; Myriam Navarro; Katia Fernández; Waleska Vera; María José Larrazábal; Iván Neira; Adrián Paredes; Manuel Osorio; Osvaldo Yáñez; et al. (Plants)
Chilean Schinus molle has been used in traditional medicine for effects such as antibacterial, antifungal, anti-inflammatory, analgesic, antiviral, antitumoral, antioxidant, antispasmodic, astringent, antipyretic, cicatrizant, cytotoxic, diuretic, among others. In this study, we evaluated the pharmacological potential of Schinus molle seed essential oil extract (SM_EO) through in vitro and in silico approaches. In vitro, the antioxidant potential was analyzed, and antitumor activity was evaluated in non-tumor and human epithelial tumor cell lines. Caenorhabditis elegans was used as a model for evaluating toxicity, and the chemical composition of the SM_EO was analyzed using gas chromatography–mass spectrometry. The oil contained four major monoterpenes: α-phellandrene (34%), β-myrcene (23%), limonene (13%), and β-phellandrene (7%). Based on quantum mechanical calculations, the reactivity of the molecules present in the SM_EO was estimated. The results indicated that α- phellandrene, β-phellandrene, and β-myrcene showed the highest nucleophilic activity. In addition, the compounds following these as candidates for antioxidant and antiproliferative activities were α-phellandrene, β-phellandrene, ρ-cymene, sabinene, caryophyllene, l-limonene, and α-pinene, highlighting β-myrcene. Based on ADME-Tox properties, it is feasible to use these compounds as new drug candidates. Moreover, the antibacterial activity MIC value obtained for B. cereus was equivalent to 2 μg/mL, and for Y. enterocolitica, S. enteritidis, and S. typhimurium, the MIC value was 32.5 μg/μL. SM_EO could selectively inhibit the proliferation of human epithelial mammary tumor MCF7 cells treated with SM_EOs at 64 and 16 ug/mL—a significant increase in BCL-2 in a dose-dependent manner—and showed low toxicity against Caenorhabditis elegans (from 10 to 0.078 mg·mL−1). These findings suggest that SM_EO may be a potential source of bioactive compounds, encouraging further investigation for applications in veterinary medicine, cosmetics, and sanitation.